Modified method for ultimate limit state determination of main pipeline in the presence of corrosion damages - Астанін, В.В.; Бородачов, М.М.; Богдан, С.Ю. (Proceedings of National Aviation University (archive), 2010)
The problem for ultimate limit state determination of large-diameter pipe in the presence of corrosion damages was considered and a modified method of its evaluation applying finite elements method was proposed. Some samples were analyzed.